IMPLEMENTASI PROGRAM DANA BANTUAN PEMBERDAYAAN USAHA GARAM RAKYAT (PUGAR) DALAM RANGKA PENGEMBANGAN WIRAUSAHA GARAM RAKYAT (Studi Pada Dinas Kelautan Dan Perikanan Kabupaten Sumenep) - Bagus Ananda Kurniawan (UII, 2016)
This qualitative research method to describe and analyze a policy which aims to empower the people in the salt business Sumenep portrayed through the study of Program Implementation Assistance Fund for Empowerment of People's Salt (PUGAR) with an emphasis on policy implementation model consisting Grindle of contents (contents of policy) and (contexts of policy) policy implementation. Empowerment of People's Salt (PUGAR) sourced from the state budget is a development program that focused on improving the welfare of the farmers of salt, as well as increased production and product quality salt. The research findings indicate that Content Policy (Of Content Policy) covers Salt Empowerment of People (PUGAR) has been established through the minister of marine and fisheries regulation number 41 of 2011 on guidelines for the implementation of the National Program for Community Empowerment and Fisheries. implementation of the policy (the Context of Policy) includes a companion team PUGAR Department of Marine and Fisheries Sumenep identifying the existence and location of the land to the group PUGAR group that has submitted a proposal for assistance and workshops as well as socialization PUGAR annually. The conclusion of the study include the provision of information about program implementation PUGAR up the thawing process is less clear PUGAR assistance received by a group of farmers salt (KUGAR). Salt farmer business groups of people (KUGAR) Recipient PUGAR each year hoping PUGAR funds disbursed prior to the production of salt, this PUGAR funds transferred to a bank account belonging to a business group of salt farmers (KUGAR) and use this PUGAR funds must be adapted to the Joint Venture Plan (RUB ) contained in the Accountability Report (LPJ) proposals submitted for the salt farmers PUGAR each group of people (KUGAR). Keywords: Empowerment of People's Salt (PUGAR), Entrepreneurial Salt